El sobrepeso - obesidad como factor de riesgo para valores elevados de presión arterial en niños de 5 a 10 años de edad - Medina Alcántara, Henry Cristian (2014)
To determine if the overweight - obesity is risk factor for high blood pressure values in children from 5 to 10 years old. Materials and methods: Observational, analytical study type cases and controls, retrospective; performed at the “Centro Estatal Escuela para Menores 80045” of Laredo - Trujillo, between august 15 and december 30 of 2013. From the population study (209), the final sample was 100 children divided in two groups: 25 with high blood pressure values (cases) and 75 with normal blood pressure values (controls). The nutritional status was determined by Body Mass Index (BMI) and was classified in eutrophic (BMI≥p5 - BMI<p85), overweight (BMI≥p85 - BMI<p95) and obesity (BMI≥p95); the blood pressure (BP) was measured with a digital tensiometer and was classified in normotension (BP<p90), prehypertension (BP≥p90 - BP<p95) and hypertension (BP≥p95). Results: Overweight - obesity was present in 14 cases (56%) and 20 controls (26.6%). The overweight - obesity as risk factor for high blood pressure values presented a very significant difference (p<0.05) and OR of 3.5 (IC to 95% of 1.20 - 6.87). Conclusion: The overweight - obesity is risk factor for high blood pressure values in children 5 to 10 years old